Pencemaran Nama Baik Ditinjau dari UU ITE dalam Perspektif Kebebasan Berpendapat - Andika Jayanegara (UNISBA Press, 2024)
Abstract. The rapid development of information technology, especially the internet, has facilitated the achievement of personal and professional goals, often leading to both legal and illegal activities aimed at maximizing profits. Unfortunately, the negative impact of this technological progress, particularly in cyberspace, is increasingly evident in modern society. One such impact is the rise of cybercrime, including defamation, which is addressed in Article 27 Paragraph (3) of the ITE Law. This article refers to the defamation provisions in Article 310 of the Criminal Code, encompassing the elements of the crime, justification, and the general doctrine for its application.A notable case involving the ITE Law is the legal dispute between Haris Azhar, S.H., M.H., and Fatia Maulidyanti, S.H., against Luhut Binsar Pandjaitan. This case revolves around a YouTube video on the